Respuesta :

[tex]\mathbb{PROBLEM : } [/tex]

==========================================

[tex] \tt10. Simplify : \: (4x2 - 2x) - (-5x2 - 8x).[/tex]

==========================================

[tex]\mathbb{ANSWER : }[/tex]

[tex] \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \tt \underline \red{ 3x(3x + 2)}[/tex]

==========================================

[tex]\mathbb{SOLUTION : }[/tex]

[tex] \: \: \: \: \: \: \: \: \: \tt(4x2 - 2x) - (-5x2 - 8x)[/tex]

[tex] \: \: \: \: \: \: \: \: \: \tt= 4x2 - 2x + 5x2 + 8x[/tex]

[tex] \: \: \: \: \: \: \: \: \: \tt{= 4x2 + 5x2 - 2x + 8x}[/tex]

[tex] \: \: \: \: \: \: \: \: \: \tt{= 9x2 + 6x}[/tex]

[tex] \tt{Answer: } \tt \underline \red{3x(3x + 2)}[/tex]

┌─────── ∘°❁°∘ ───────┐

CarryOnLearning ૮₍˶ᵔ ᵕ ᵔ˶₎ა

︎︎└─────── °∘❁∘° ───────┘